Importance of the "thinking through other minds" process explored through motor correlates of motivated social interactions. (28th May 2020) - Mouras, Harold
Abstract: We wanted to gather recent results supporting the idea of the central role of sharing agency in socioaffective and motivational information processing. Here, we want to support the idea that this process is quite arbitrary, early in the temporal chain of processes and not only influence the psychological, but also the motor correlates of socioaffective information processes.